Dark soliton generation using dual brillouin fiber laser in a fiber optic ring resonator - Hanim, S. F.; Ali, J.; Yupapin, P. P. (My University, 2010)
Stable dark soliton pulses have been successfully generated in an erbium doped dispersion compensated fiber (DCF) using an enhanced dual Brillouin fiber laser (DBFL) scheme. Multidark soliton pulses generation in an S-band erbium doped depressed cladding fiber (DC-EDF) using a multiwavelength Brillouin fiber laser (MW-BFL). Configuration has also been successfully demonstrated. The hybrid amplification from the 300 mW power of Raman pump (RP), 7.7 km long DCF, and 30 m DC-EDF that is being pumped bidirectionally results in a stable multiwavelength Brillouin peaks in the S-band region. Results obtained shows that the insertion of linear gain medium with bidirectional pumping of the DC-EDF into the cavity gives significant amplification and promotes the formation of stokes peaks in the S-band region. The number of Brillouin peaks generated is closely dependent on the DBFL and MW-BFL configuration, the Brillouin pump (BP) signal wavelength, the BP coupling ratio, and the RP power. © 2010 Wiley Periodicals, Inc.
Keywords: Brillouin pump; Dark soliton; Depressed cladding fiber; Multi soliton S-band erbium doped fiber; Raman pump; Stimulated Brillouin Scattering; Stokes peaks